Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Adolescent with painful vesicular otitis and vertigo. - Conversano, Ester; Cozzi, Giorgio; Poropat, Federico; Di Mascio, Alberto; Salis, Simona; Grasso, Domenico Leonardo; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2019)

Antibodies reacting to mimotopes of Simian virus 40 large T antigen, the viral oncoprotein, in sera from children. - Mazzoni, Elisa; Frontini, Francesca; Rotondo, John Charles; Zanotta, Nunzia; Fioravanti, Arianna; Minelli, Francesca; Torreggiani, Elena; Campisciano, Giuseppina; Marcuzzi, Annalisa; Guerra, Giovanni; Tommasini, Alberto; Touzé, Antoine; et al. (J Cell Physiol, 2019)
Recent data indicate that the Simian virus 40 (SV40) infection appears to be transmitted in humans independently from early SV40-contaminated antipolio vaccines. Serum antibodies against SV40 large T antigen (Tag) were analyzed in children/adolescents and young adults. To investigate antibodies reacting to SV40 Tag antigens, serum samples ( n = 812) from children and young adults were analyzed by indirect ELISAs using specific SV40 Tag mimotopes. Mimotopes were synthetic peptides corresponding to SV40 Tag epitopes. In sera ( n = 412) from healthy children up to 17 years old, IgG antibodies against SV40 Tag mimotopes reached an overall prevalence of 15%. IgM antibodies against SV40 Tag were detected in sera of children 6-8 months old confirming and extending the knowledge that SV40 seroconversion occurs early in life. In children/adolescents affected by different diseases ( n = 180) SV40 Tag had a prevalence of 18%, being the difference no significant compared to healthy subjects ( n = 220; 16%) of the same age. Our immunological data indicate that SV40 circulates in children and young adults, both in healthy conditions and affected by distinct diseases. The IgM detection in sera from healthy children suggests that the SV40 infection/seroconversion occurs early in life (>6 months). Our immunological data support the hypothesis that SV40, or a closely related still unknown polyomavirus, infects humans. The SV40 seroprevalence is lower than common polyomaviruses, such as BKPyV and JCPyV, and other new human polyomaviruses. In addition, our immunological surveillance indicates a lack of association between different diseases, considered herein, and SV40.

Activation of hepatic stem cells compartment during hepatocarcinogenesis in a HBsAg HBV-transgenic mouse model. - Anfuso, Beatrice; El-Khobar, Korri E; Ie, Susan I; Avellini, Claudio; Radillo, Oriano; Raseni, Alan; Tiribelli, Claudio; Sukowati, Caecilia H C (Sci Rep, 2018)
Chronic infection of Hepatitis B Virus (HBV) is one of the highest risk factors of hepatocellular carcinoma (HCC). The accumulation of HBV surface antigen (HBsAg) into hepatocytes induces inflammation and oxidative stress, impairing their replicative ability and allowing the activation of the hepatic stem cells (SC) compartment. This study aimed to understand the involvement of SC during hepatocarcinogenesis in HBsAg-related liver damage, from early injury until HCC. HBsAg-transgenic (TG) and wild type (WT) mouse were followed at several stages of the liver damage: inflammation, early hepatocytes damage, dysplasia, and HCC. Serum transaminases, liver histology, and diagnostic data were collected. The expressions of SC and cancer stem cells (CSC) markers was analyzed by RT-qPCR, immunohistochemistry and Western blot. Starting from 3 months, TG animals showed a progressive liver damage characterized by transaminases increase. The up-regulations of SCs markers Cd34 and Sca-1 started from the beginning of the inflammatory stage while progressive increase of Krt19 and Sox9 and CSCs markers Epcam and Cd133 from early hepatic injury. The expressions of Cd133, Cd34, and Afp were significantly higher in HCC compared to paired non-HCC tissue, in contrast to Epcam and Krt19. Western blot and IHC confirmed the positivity of Cd34 and Cd133 in small cells subpopulation.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

Acute small bowel obstruction in a child with a strict raw vegan diet. - Amoroso, Stefano; Scarpa, Maria-Grazia; Poropat, Federico; Giorgi, Rita; Murru, Flora Maria; Barbi, Egidio (Arch Dis Child, 2018)

Adenomyomatosis of the Gallbladder as a Cause of Recurrent Abdominal Pain. - Agrusti, Anna; Gregori, Massimo; Salviato, Tiziana; Codrich, Daniela; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abdominal Pain; Adenomyoma; Adolescent; Biopsy, Needle; Cholecystectomy; Diagnosis, Differential; Female; Gallbladder; Gallbladder Neoplasms; Humans; Immunohistochemistry; Recurrence; Risk Assessment; Severity of Illness Index; Ultrasonography, Doppler

Adolescent with intermittent haematuria. - Pillon, Roberto; Pennesi, Marco; Rabach, Ingrid; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2018)

Afebrile seizures in infants: Never forget magnesium! - Minute, Marta; Ventura, Giovanna; Giorgi, Rita; Faletra, Flavio; Costa, Paola; Cozzi, Giorgio (J Paediatr Child Health, 2018)

Alcohol use and burden for 195 countries and territories, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet, 2018)
BACKGROUND: Alcohol use is a leading risk factor for death and disability, but its overall association with health remains complex given the possible protective effects of moderate alcohol consumption on some conditions. With our comprehensive approach to health accounting within the Global Burden of Diseases, Injuries, and Risk Factors Study 2016, we generated improved estimates of alcohol use and alcohol-attributable deaths and disability-adjusted life-years (DALYs) for 195 locations from 1990 to 2016, for both sexes and for 5-year age groups between the ages of 15 years and 95 years and older. METHODS: Using 694 data sources of individual and population-level alcohol consumption, along with 592 prospective and retrospective studies on the risk of alcohol use, we produced estimates of the prevalence of current drinking, abstention, the distribution of alcohol consumption among current drinkers in standard drinks daily (defined as 10 g of pure ethyl alcohol), and alcohol-attributable deaths and DALYs. We made several methodological improvements compared with previous estimates: first, we adjusted alcohol sales estimates to take into account tourist and unrecorded consumption; second, we did a new meta-analysis of relative risks for 23 health outcomes associated with alcohol use; and third, we developed a new method to quantify the level of alcohol consumption that minimises the overall risk to individual health. FINDINGS: Globally, alcohol use was the seventh leading risk factor for both deaths and DALYs in 2016, accounting for 2·2% (95% uncertainty interval [UI] 1·5-3·0) of age-standardised female deaths and 6·8% (5·8-8·0) of age-standardised male deaths. Among the population aged 15-49 years, alcohol use was the leading risk factor globally in 2016, with 3·8% (95% UI 3·2-4·3) of female deaths and 12·2% (10·8-13·6) of male deaths attributable to alcohol use. For the population aged 15-49 years, female attributable DALYs were 2·3% (95% UI 2·0-2·6) and male attributable DALYs were 8·9% (7·8-9·9). The three leading causes of attributable deaths in this age group were tuberculosis (1·4% [95% UI 1·0-1·7] of total deaths), road injuries (1·2% [0·7-1·9]), and self-harm (1·1% [0·6-1·5]). For populations aged 50 years and older, cancers accounted for a large proportion of total alcohol-attributable deaths in 2016, constituting 27·1% (95% UI 21·2-33·3) of total alcohol-attributable female deaths and 18·9% (15·3-22·6) of male deaths. The level of alcohol consumption that minimised harm across health outcomes was zero (95% UI 0·0-0·8) standard drinks per week. INTERPRETATION: Alcohol use is a leading risk factor for global disease burden and causes substantial health loss. We found that the risk of all-cause mortality, and of cancers specifically, rises with increasing levels of consumption, and the level of consumption that minimises health loss is zero. These results suggest that alcohol control policies might need to be revised worldwide, refocusing on efforts to lower overall population-level consumption. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Cause of Death; Commerce; Female; Global Burden of Disease; Global Health; Humans; Male; Middle Aged; Observational Studies as Topic; Population Surveillance; Prevalence; Prospective Studies; Quality-Adjusted Life Years; Retrospective Studies; Risk Assessment; Risk Factors; Sex Distribution; Young Adult

Alendronate treatment induces IL-1B expression and apoptosis in glioblastoma cell line. - Tricarico, Paola Maura; Epate, Angeladine; Celsi, Fulvio; Crovella, Sergio (Inflammopharmacology, 2018)
Alendronate (ALD), one among the nitrogen-containing bisphosphonates (NBPs), is currently used for the treatment of many pathological conditions. Unfortunately, although generally tolerated, NBPs treatment has been associated with central nervous system (CNS) adverse outcomes, such as amnesia, hallucinations and visual disturbances. So, we analyzed the effect of ALD treatment in glial cells, the main sources of cholesterol for neurons and principal cells involved in the immunological defense of the brain. We treated a glial cell line (U87-MG) with increasing doses of ALD (0.1, 1, 10, 25, 50 μM) for 48 h, aimed at evaluating the influence of this drug treatment on IL-1B expression, NLRP3 and CASP1 expression, mitochondrial activity and apoptotic cell death. We observed that ALD treatment, at the higher concentrations, induced a significant increase of IL-1B, NLRP3, CASP1 expression, provoked apoptosis and also mitochondrial damage in U87-MG. Considering the reported CNS adverse outcomes of NBPs treatment, our results confirm ALD side-effects on glial cell model.
Keywords: Alendronate; Apoptosis; Brain; Cell Line, Tumor; Diphosphonates; Glioblastoma; Humans; Interleukin-1beta; Neuroglia

Anaphylaxis in atypical cold urticaria: case report and review of literature. - Benelli, Elisa; Longo, Giorgio; Barbi, Egidio; Berti, Irene (Ital J Pediatr, 2018)
BACKGROUND: Cold-induced urticaria is a kind of physical urticaria characterized by the appearance of wheals after exposure to cold. The atypical form is a rare sub-type characterized by appearance of hives even in areas not directly exposed to the cold and by a negative cold stimulation test. Its diagnosis is often challenging because of the lack of specific tests and it is usually based on the patient's clinical history. Hypotension due to generalized exposure to the cold is described both in the typical and the atypical forms. CASE PRESENTATION: We describe a 9-year-old boy who, at the beginning of the summer after the first swim in the sea, developed generalized urticaria, dyspnea, conjunctival hyperemia, blurred vision and loss of strength. The child was treated with intramuscular steroid and intravenous antihistamine, and the symptoms quickly resolved. Insect bite, contact with fish and drug ingestion were denied, and no unusual food had been eaten before the swim. A tentative diagnosis was made of either aquagenic urticaria or cold urticaria, but the specific tests were negative. Although the cause was unknown, prophylactic treatment with antihistamines was prescribed but in spite of this, wheals developed all over the body, after every swim in the sea. The child then came to our attention and relying on clinical history a diagnosis of atypical cold urticaria was made: development of hives even in areas not directly exposed to cold and a negative response to the cold stimulation test, are the characteristic features of this rare form of cold urticaria. CONCLUSION: Atypical cold urticaria should be suspected in all cases of anaphylaxis related to cold exposure (i.e. contact with water) with a negative cold stimulation test.
Keywords: Anaphylaxis; Child; Cold Temperature; Humans; Male; Swimming; Urticaria

Antibody response to polyomavirus primary infection: high seroprevalence of Merkel cell polyomavirus and lymphoid tissue involvement. - Cason, Carolina; Monasta, Lorenzo; Zanotta, Nunzia; Campisciano, Giuseppina; Maestri, Iva; Tommasino, Massimo; Pawlita, Michael; Villani, Sonia; Comar, Manola; Delbue, Serena (J Neurovirol, 2018)
Human polyomaviruses (HPyVs) asymptomatically infect the human population establishing latency in the host, and their seroprevalence can reach 90% in healthy adults. Few studies have focused on the pediatric population, and there are no reports regarding the seroprevalence of all the newly isolated HPyVs among Italian children. Therefore, we investigated the frequency of serum antibodies against 12 PyVs in 182 immunocompetent children from Northeast Italy, by means of a multiplex antibody detection system. Additionally, secondary lymphoid tissues were collected to analyze the presence of HPyV DNA sequences using a specific real-time PCRs or PCRs. Almost 100% of subjects were seropositive for at least one PyV. Seropositivity ranged from 3% for antibodies against simian virus 40 (SV40) in children from 0 to 3 years, to 91% for antibodies against WU polyomavirus (WUPyV) and HPyV10 in children from 8 to 17 years. The mean number of PyV for which children were seropositive increased with the increasing of age: 4 standard deviations (SD) 1.8 in the 0-3-year group, 5 (SD 1.9) in the 4-7-year group, and 6 (SD 2.2) in the 8-17-year group. JC polyomavirus (JCPyV) DNA was detected in 1% of the adenoids, WUPyV in 12% of the tonsils, and 28% of the adenoids, and Merkel cell polyomavirus (MCPyV) was present in 6 and 2% of the tonsils and adenoids, respectively. Our study gives new insights on the serological evidence of exposure to PyVs during childhood, and on their possible respiratory route of transmission.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Acute Abdominal Pain: Recognition and Management of Constipation in the Emergency Department. - Norbedo, Stefania; Bassanese, Giulia; Barbieri, Francesca; Barbi, Egidio (Pediatr Emerg Care, 2017)
OBJECTIVE: The main aim of the study was to investigate the incidence and the clinically relevant features of functional constipation in patients evaluated for acute abdominal pain in a tertiary care pediatric emergency department. METHODS: This is a retrospective study. We analyzed 4394 medical records and recorded the information (demographics, triage code, symptoms, medical history, physical evaluation, laboratory tests, radiological studies, procedures, and treatments) of all patients admitted for acute abdominal pain to the emergency department of the IRCCS Burlo Garofolo, Trieste, during 2010 to 2013. RESULTS: In this study, a quarter of patients (1020) presenting in the emergency department with acute abdominal pain were affected by functional constipation. Acute pain associated with functional constipation is generally rated from moderate to severe, and the location of the pain on physical evaluation was not a sufficient criterion to guide diagnosis. Isolated vomiting may be present in a minority of cases. Digital rectal exploration was never performed; the majority of patients were treated by means of an enema with prompt relief. Six percent of patients with constipation underwent radiological studies. CONCLUSIONS: This study confirms that the medical history provides a pivotal role in the diagnosis of functional constipation. Digital rectal exploration and x-rays should be avoided in this setting, whereas an enema plays a useful diagnostic and therapeutic role in our study patients.
Keywords: Abdominal Pain; Acute Pain; Adolescent; Child; Child, Preschool; Constipation; Emergency Service, Hospital; Enema; Female; Humans; Incidence; Infant; Male; Retrospective Studies

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Adolescent Admissions to Emergency Departments for Self-Injurious Thoughts and Behaviors. - Zanus, Caterina; Battistutta, Sara; Aliverti, Renata; Montico, Marcella; Cremaschi, Silvana; Ronfani, Luca; Monasta, Lorenzo; Carrozzi, Marco (PLoS One, 2017)
The objective of the present study was to describe the incidence and the characteristics of Self-Injurious Thoughts and Behaviors (SITBs), among adolescents aged 11-18 admitted, over a two year period, to all the Emergency Departments of a Region of North-eastern Italy through a comprehensive analysis of medical records. A two-step search was performed in the regional ED electronic database. First, we identified the cases that had been clearly diagnosed as SITBs by an Emergency Department physician. Secondly, suspect cases were detected through a keyword search of the database, and the medical records of these cases were hand screened to identify SITBs. The mean annual incidence rate of SITBs was 90 per 100,000 adolescents aged 11-18 years. Events were more frequent in females. Drug poisoning was the most frequently adopted method (54%). In 42% of cases a diagnosis of SITB was not explicitly reported by the physician. In 65% of cases adolescents were discharged within hours of admission. Only 9% of patients started a psychiatric assessment and treatment program during hospital stay. This research confirms the high incidence of SITBs among adolescents and highlights the difficulty in their proper diagnosis and management. Such difficulty is confirmed by the fact that only a few patients, even among those with a clear diagnosis, were sent for psychiatric assessment. Correct identification and management of SITB patients needs to be improved, since SITBs are an important public health problem in adolescence and one of the main risk factors for suicide.
Keywords: Adolescent; Child; Female; Humans; Incidence; Italy; Male; Medical Records; Patient Admission; Retrospective Studies; Self-Injurious Behavior; Sex Factors; Suicidal Ideation; Suicide, Attempted

Alternative functions of the complement protein C1q at embryo implantation site. - Agostinis, Chiara; Tedesco, Francesco; Bulla, Roberta (J Reprod Immunol, 2017)
Complement component C1q is one of the recognition molecules of the complement system which can serve several functions unrelated to complement activation. This molecule is produced at foeto-maternal interface by macrophages as wells as by decidual endothelial cells and invading trophoblast. Foetal trophoblast cells migrating through the decidua in the early stages of pregnancy synthesize and express C1q on their surface, which is actively involved in promoting trophoblast endovascular and interstitial invasion of the decidua. These functions are mediated by two cell surface receptors, gC1qR and α4β1 integrin, which promote trophoblast adhesion and migration through the activation of ERK1/2 MAPKs. C1q mice manifest increased frequency of foetal resorption, reduced foetal weight, and smaller litter size when compared to their wild-type counterparts, suggesting that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia. C1q acts also as a strong angiogenic factor and promotes neovascularization. These studies suggest novel and unexpected roles of this complement component in physiological and pathological pregnancies.
Keywords: Animals; Complement C1q; Decidua; Embryo Implantation; Extracellular Signal-Regulated MAP Kinases; Female; Humans; Integrin alpha4beta1; Mice; Mice, Knockout; Neovascularization, Physiologic; Pre-Eclampsia; Pregnancy; Trophoblasts; Vascular Remodeling

Amniocentesis and chorionic villus sampling in HIV-infected pregnant women: a multicentre case series. - Floridia, M; Masuelli, G; Meloni, A; Cetin, I; Tamburrini, E; Cavaliere, A F; Dalzero, S; Sansone, M; Alberico, S; Guerra, B; Spinillo, A; Chiadò Fiorio Tin, M; et al. (BJOG, 2017)
OBJECTIVES: To assess in pregnant women with HIV the rates of amniocentesis and chorionic villus sampling (CVS), and the outcomes associated with such procedures. DESIGN: Observational study. Data from the Italian National Program on Surveillance on Antiretroviral Treatment in Pregnancy were used. SETTING: University and hospital clinics. POPULATION: Pregnant women with HIV. METHODS: Temporal trends were analysed by analysis of variance and by the Chi-square test for trend. Quantitative variables were compared by Student's t-test and categorical data by the Chi-square test, with odds ratios and 95% confidence intervals calculated. MAIN OUTCOME MEASURES: Rate of invasive testing, intrauterine death, HIV transmission. RESULTS: Between 2001 and 2015, among 2065 pregnancies in women with HIV, 113 (5.5%) had invasive tests performed. The procedures were conducted under antiretroviral treatment in 99 cases (87.6%), with a significant increase over time in the proportion of tests performed under highly active antiretroviral therapy (HAART) (100% in 2011-2015). Three intrauterine deaths were observed (2.6%), and 14 pregnancies were terminated because of fetal anomalies. Among 96 live newborns, eight had no information available on HIV status. Among the remaining 88 cases with either amniocentesis (n = 75), CVS (n = 12), or both (n = 1), two HIV transmissions occurred (2.3%). No HIV transmission occurred among the women who were on HAART at the time of invasive testing, and none after 2005. CONCLUSIONS: The findings reinforce the assumption that invasive prenatal testing does not increase the risk of HIV vertical transmission among pregnant women under suppressive antiretroviral treatment. TWEETABLE ABSTRACT: No HIV transmission occurred among women who underwent amniocentesis or CVS under effective anti-HIV regimens.
Keywords: Adult; Amniocentesis; Analysis of Variance; Anti-Retroviral Agents; Chi-Square Distribution; Chorionic Villi Sampling; Female; Fetal Death; HIV Infections; Humans; Infectious Disease Transmission, Vertical; Odds Ratio; Pregnancy; Pregnancy Complications, Infectious

ANCA-associated vasculitis in childhood: recent advances. - Calatroni, Marta; Oliva, Elena; Gianfreda, Davide; Gregorini, Gina; Allinovi, Marco; Ramirez, Giuseppe A; Bozzolo, Enrica P; Monti, Sara; Bracaglia, Claudia; Marucci, Giulia; Bodria, Monica; Sinico, Renato A; et al. (Ital J Pediatr, 2017)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are rare systemic diseases that usually occur in adulthood. They comprise granulomatosis with polyangiitis (GPA, Wegener's), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss syndrome). Their clinical presentation is often heterogeneous, with frequent involvement of the respiratory tract, the kidney, the skin and the joints. ANCA-associated vasculitis is rare in childhood but North-American and European cohort studies performed during the last decade have clarified their phenotype, patterns of renal involvement and their prognostic implications, and outcome. Herein, we review the main clinical and therapeutic aspects of childhood-onset ANCA-associated vasculitis, and provide preliminary data on demographic characteristics and organ manifestations of an Italian multicentre cohort.
Keywords: Age Distribution; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Child; Child, Preschool; Churg-Strauss Syndrome; Female; Granulomatosis with Polyangiitis; Humans; Incidence; Male; Microscopic Polyangiitis; Rare Diseases; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Antibiotic Prophylaxis for Urinary Tract Infection-Related Renal Scarring: A Systematic Review. - Hewitt, Ian K; Pennesi, Marco; Morello, William; Ronfani, Luca; Montini, Giovanni (Pediatrics, 2017)
CONTEXT: Acute pyelonephritis may result in renal scarring. Recent prospective studies have shown a small benefit of antibiotic prophylaxis in preventing symptomatic and febrile urinary tract infections (UTIs), while being underpowered to detect any influence in prevention of renal damage. OBJECTIVES: Review of the literature and a meta-analysis to evaluate the effect of antibiotic prophylaxis on UTI-related renal scarring. DATA SOURCES: Medline, Embase, and Cochrane Controlled Trials Register electronic databases were searched for studies published in any language and bibliographies of identified prospective randomized controlled trials (RCTs) performed and published between 1946 and August 2016. STUDY SELECTION: Subjects 18 years of age or younger with symptomatic or febrile UTIs, enrolled in prospective RCTs of antibiotic prophylaxis where Tc dimercaptosuccinic acid scans were performed at entry into the study and at late follow-up to detect new scar formation. DATA EXTRACTION: The literature search, study characteristics, inclusion and exclusion criteria, and risk of bias assessment were independently evaluated by 2 authors. RESULTS: Seven RCTs (1427 subjects) were included in the meta-analysis. Our results show no influence of antibiotic prophylaxis in preventing renal scarring (pooled risk ratio, 0.83; 95% confidence interval, 0.55-1.26) as did a subanalysis restricted to those subjects with vesicoureteral reflux (pooled risk ratio, 0.79; 95% confidence interval, 0.51-1.24). LIMITATIONS: Limitations include the small number of studies, short duration of follow-up, and insufficient children with high-grade dilating reflux and/or renal dysplasia enrolled in the studies. CONCLUSIONS: Antibiotic prophylaxis is not indicated for the prevention of renal scarring after a first or second symptomatic or febrile UTI in otherwise healthy children.
Keywords: Acute Disease; Antibiotic Prophylaxis; Child; Cicatrix; Humans; Kidney; Pyelonephritis; Urinary Tract Infections

Antiretroviral Treatment in HIV-1-Positive Mothers: Neurological Implications in Virus-Free Children. - Coelho, Antônio Victor Campos; Tricarico, Paola Maura; Celsi, Fulvio; Crovella, Sergio (Int J Mol Sci, 2017)
Since the worldwide introduction of antiretroviral therapy (ART) in human immunodeficiency virus type 1, HIV-1-positive mothers, together with HIV-1 testing prior to pregnancy, caesarian birth and breastfeeding cessation with replacement feeding, a reduction of HIV-1 mother-to-child transmission (MTCT) has been observed in the last few years. As such, an increasing number of children are being exposed in utero to ART. Several questions have arisen concerning the neurological effects of ART exposure in utero, considering the potential effect of antiretroviral drugs on the central nervous system, a structure which is in continuous development in the fetus and characterized by great plasticity. This review aims at discussing the possible neurological impairment of children exposed to ART in utero, focusing attention on the drugs commonly used for HIV-1 MTCT prevention, clinical reports of ART neurotoxicity in children born to HIV-1-positive mothers, and neurologic effects of protease inhibitors (PIs), especially ritonavir-"boosted" lopinavir (LPV/r) in cell and animal central nervous system models evaluating the potential neurotoxic effect of ART. Finally, we present the findings of a meta-analysis to assess the effects on the neurodevelopment of children exposed to ART in utero.
Keywords: Animals; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Disease Management; Disease Models, Animal; Epigenesis, Genetic; Female; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Maternal Exposure; Meta-Analysis as Topic; Mothers; Neurodevelopmental Disorders; Pregnancy; Prenatal Exposure Delayed Effects

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Authors' Reply to M.S. Raghuraman: "Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate". - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives; Infant

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Avoiding Ethanol Presence in DNA Samples Enhances the Performance of Ultraviolet Resonance Raman Spectroscopy Analysis. - Cammisuli, Francesca; Pascolo, Lorella; Morgutti, Marcello; Gessini, Alessandro; Masciovecchio, Claudio; D'Amico, Francesco (Appl Spectrosc, 2017)
Ethanol is an essential chemical reagent in DNA preparation as its use increases the yield of extraction. All methodologies for DNA isolation involve the use of ethanol in order to prevent DNA dissolution in water and to optimize the binding of DNA to chromatographic membranes. In this note, we show how the presence of ethanol traces in DNA aqueous solution affects ultraviolet Raman spectra, leading to possible misinterpretations. We report a simple method to remove the ethanol Raman features from the spectra, based on heating the DNA sample at 80 ℃, followed by a slow cooling procedure.
Keywords: DNA; Ethanol; Female; Humans; Placenta; Pregnancy; Spectrophotometry, Ultraviolet; Spectrum Analysis, Raman

Abnormal expression of leiomyoma cytoskeletal proteins involved in cell migration. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Athanasakis, Emmanouil; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Rep, 2016)
Uterine leiomyomas are monoclonal tumors. Several factors are involved in the neoplastic transformation of the myometrium. In our study we focused on dysregulated cytoskeletal proteins in the leiomyoma as compared to the myometrium. Paired tissue samples of ten leiomyomas and adjacent myometria were obtained and analyzed by two‑dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification, and western blotting for 2-DE data validation. The values of ten cytoskeletal proteins were found to be significantly different: eight proteins were upregulated in the leiomyoma and two proteins were downregulated. Three of the upregulated proteins (myosin regulatory light polypeptide 9, four and a half LIM domains protein 1 and LIM and SH3 domain protein 1) are involved in cell migration, while downregulated protein transgelin is involved in replicative senescence. Myosin regulatory light polypeptide 9 (MYL9) was further validated by western blotting because it is considered to be a cell migration marker in several cancers and could play a key role in leiomyoma development. Our data demonstrate significant alterations in the expression of cytoskeletal proteins involved in leiomyoma growth. A better understanding of the involvement of cytoskeletal proteins in leiomyoma pathogenesis may contribute to the identification of new therapeutic targets and the development of new pharmacological approaches.

Achieving early functional auditory access in paediatric cochlear implantation. - Orzan, E; Muzzi, E; Marchi, R; Falzone, C; Battelino, S; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Cochlear implantation (CI) is a viable option for providing access to auditory stimulation in severe-to-profound hearing loss/impairment of cochlear origin. It has been demonstrated that CI is safe and effective for deaf children. Younger age at activation after CI is linked with better outcomes. It is important to study variables and issues that can interfere with an early fitting and access to sound after CI. They range from patient characteristics, family compliance and support, to technical, medical or organisational problems. A SWOT analysis and a subsequent TOWS matrix was conducted to discuss issues and propose recommendations to be considered when operating an early switch on of the CI.

Achieving effective hearing aid fitting within one month after identification of childhood permanent hearing impairment. - Bastanza, G; Gallus, R; De Carlini, M; Picciotti, P M; Muzzi, E; Ciciriello, E; Orzan, E; Conti, G (Acta Otorhinolaryngol Ital, 2016)
Diagnosis of child permanent hearing impairment (PHI) can be made with extreme timeliness compared to the past thanks to improvements in PHI identification through newborn hearing screening programmes. It now becomes essential to provide an effective amplification as quickly as possible in order to restore auditory function and favour speech and language development. The early fitting of hearing aids and possible later cochlear implantation indeed prompts the development of central auditory pathways, connections with secondary sensory brain areas, as well as with motor and articulatory cortex. The aim of this paper is to report the results of a strategic analysis that involves identification of strengths, weaknesses, opportunities and threats regarding the process of achieving early amplification in all cases of significant childhood PHI. The analysis is focused on the Italian situation and is part of the Italian Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children".

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

Acute myelitis as presenting symptom of HIV-HTLV-1 co-infection. - Cucca, A; Stragapede, L; Antonutti, L; Catalan, M; Caracciolo, I; Valentinotti, Romina; Granato, A; D'Agaro, P; Manganotti, P (J Neurovirol, 2016)
A 21-year-old woman presented with acute-onset spastic paraparesis. The MRI spinal scan revealed a contrast-enhanced T2 hyperintensity between C5-T2. The most common neurotropic pathogens were excluded by first level tests. Under suspicion of an acute immune-mediated myelitis, a corticosteroid therapy was administered. However, a seropositivity for both human immunodeficiency virus (HIV) type 1 and human T-lymphotropic virus (HTLV) subsequently emerged. An antiretroviral therapy was started while steroids discontinued. Patient's clinical conditions remained unchanged. HIV-HTLV-1 co-infection should be included in the differential diagnosis of any acute myelitis, even in patients with a preserved immune status and no risk factors.

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Association between Congenital Lung Malformations and Lung Tumors in Children and Adults. A Systematic Review. - Casagrande, Arianna; Pederiva, Federica (J Thorac Oncol, 2016)
INTRODUCTION: The appropriate management of asymptomatic congenital pulmonary malformations (CPMs) remains controversial. Prophylactic surgery is recommended to avoid the risk for development of pulmonary infections and to prevent the highly debated development of malignancy. However, the true risk for development of malignancy remains unknown. A systematic review analyzed all cases in which lung tumors associated with CPMs in both the pediatric and adult populations were described. METHODS: A comprehensive literature search was carried out; it included all the cases in which an association between CPMs and malignant pulmonary lesions was reported. RESULTS: In all, 134 publications were eligible for inclusion. In 168 patients CPM was found associated with lung tumor. The diagnosis was made in 76 children at a mean age of 3.68 ± 3.4, whereas in the adult population (n = 92) it was made at a mean age of 44.62 ± 16.09. Cough was the most frequent presenting symptom both in children and in adults. Most of the patients underwent lobectomy. The tumor most often associated with CPM was pleuropulmonary bastoma in children (n = 31) and adenocarcinoma (n = 20) or bronchioloalveolar carcinoma (n = 20) in adults. The CPM most frequenty associated with tumors in children was congenital cystic adenomatoid malformation (n = 37), especially type 1 (n = 21), whereas in adults it was bronchogenic cyst (n = 25), followed by congenital cystic adenomatoid malformation (n = 21). CONCLUSIONS: CPMs should be followed up and never underestimated because they may conceal a tumor. Apparently, there is no age limit for malignant progression of CPMs and no limit of the interval between first detection of the CPM and appearance of the associated tumor.

Association between p21 Ser31Arg polymorphism and the development of cervical lesion in women infected with high risk HPV. - Lima, Géssica; Santos, Erinaldo; Angelo, Hildson; Oliveira, Micheline; Heráclio, Sandra; Leite, Fernanda; de Melo, Celso; Crovella, Sergio; Maia, Maria; Souza, Paulo (Tumour Biol, 2016)
Infection by high-risk human papillomavirus (HR-HPV) and single nucleotide polymorphism (SNP) in genes involved in cell cycle control, as p21 and p27, are important factors in the development of different types of human cancers. This study aims at investigating whether both the p21 Ser31Arg and p27 V109G polymorphisms are associated with susceptibility to the development of cervical lesions in women HR-HPV positive. We analyzed 132 women HPV positive and with cervical lesions or CC and 154 healthy control (HPV negative and without cervical lesions). p21 Ser31Arg and p27 V109G polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and sequencing. The p21 31Arg allele was associated with susceptibility for the development of cervical lesions (P* = 0.0009), while p27 V109G polymorphism showed no significant differences for this association (P* = 0.89). However, the combined effect of the polymorphisms showed that the presence of the CC genotype (SNP p21 Ser31Arg) conferred protection for the development of cervical lesions (OR = 0.39). p21 Ser31Arg and p27 V109G polymorphisms were not associated with the grade of cervical lesions (CINI, CINII, and CINIII) or CC (P* > 0.05). The HR-HPV more frequent in this study were of 16 (57.6 %) and 18 (37.1 %) types; however, no association was observed when both polymorphisms and risk factors analyzed were compared (P* > 0.05). Our findings suggest a possible association between p21 Ser31tabArg polymorphism and susceptibility to the development of cervical lesions in women from Pernambuco. Brazil.

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

Abnormal cytoplasmic extensions associated with active αIIbβ3 are probably the cause for macrothrombocytopenia in Glanzmann thrombasthenia-like syndrome. - Hauschner, Hagit; Mor-Cohen, Ronit; Messineo, Stefania; Mansour, Wissam; Seligsohn, Uri; Savoia, Anna; Rosenberg, Nurit (Blood Coagul Fibrinolysis, 2015)
Mutations in the ITGA2B or ITGB3 genes that encode for the αIIbβ3 platelet integrin usually cause Glanzmann thrombasthenia, a severe autosomal recessive bleeding disorder characterized by absence of platelet aggregation, but normal platelet number and size. Several rare mutations cause a Glanzmann-like syndrome which manifests macrothrombocytopenia and usually displays autosomal dominant inheritance. The exact mechanism causing Glanzmann-like syndrome is unknown. One typical example of Glanzmann-like mutations causes deletion of 40 amino acids (p.647-686) in the β3 β-tail domain (βTD_del) that was found in the heterozygous state in Italian and Japanese families. A second example is a missense mutation, C560R, located in the epidermal growth factor-like domain, found in the homozygous state in a French patient. Both mutations cause constitutive activation of αIIbβ3, but differ in their surface expression. In the current study, we generated cultured cells expressing β3-βTD_del or β3-C560R mutations along with wild-type αIIb, and examined the cells' ability to create tubulin-dependent protrusions compared to cells expressing wild-type αIIbβ3. Unlike cells expressing wild-type αIIbβ3, cells harboring each of the mutations exhibited abnormal cytoplasmic extensions on immobilized fibrinogen or Von Willebrand factor, which resembled extensions formed in megakaryocyte leading to proplatelets. Moreover, we showed that formation of abnormal extensions occurred also in wild-type αIIbβ3 cells when activated by activating antibody. These results suggest that the active conformation of αIIbβ3 can induce cytoskeletal rearrangements that lead to impaired proplatelet formation.
Keywords: Animals; Cell Line; Cricetinae; Cytoskeleton; DNA, Complementary; Fibrinogen; Genetic Vectors; Humans; Integrin alpha2; Integrin beta3; Megakaryocytes; Mesocricetus; Microtubules; Mutation, Missense; Platelet Glycoprotein GPIIb-IIIa Complex; Protein Conformation; Protein Interaction Mapping; Protein Structure, Tertiary; Recombinant Fusion Proteins; Sequence Deletion; Thrombasthenia; Tubulin; von Willebrand Factor

ACTN1-related thrombocytopenia: identification of novel families for phenotypic characterization. - Bottega, Roberta; Marconi, Caterina; Faleschini, Michela; Baj, Gabriele; Cagioni, Claudia; Pecci, Alessandro; Pippucci, Tommaso; Ramenghi, Ugo; Pardini, Simonetta; Ngu, Loretta; Baronci, Carlo; Kunishima, Shinji; et al. (Blood, 2015)
Inherited thrombocytopenias (ITs) are a heterogeneous group of syndromic and nonsyndromic diseases caused by mutations affecting different genes. Alterations of ACTN1, the gene encoding for α-actinin 1, have recently been identified in a few families as being responsible for a mild form of IT (ACTN1-related thrombocytopenia; ACTN1-RT). To better characterize this disease, we screened ACTN1 in 128 probands and found 10 (8 novel) missense heterozygous variants in 11 families. Combining bioinformatics, segregation, and functional studies, we demonstrated that all but 1 amino acid substitution had deleterious effects. The clinical and laboratory findings of 31 affected individuals confirmed that ACTN1-RT is a mild macrothrombocytopenia with low risk for bleeding. Low reticulated platelet counts and only slightly increased serum thrombopoietin levels indicated that the latest phases of megakaryopoiesis were affected. Given its relatively high frequency in our cohort (4.2%), ACTN1-RT has to be taken into consideration in the differential diagnosis of ITs.
Keywords: Actinin; Adolescent; Adult; Aged; Aged, 80 and over; Blood Platelets; Case-Control Studies; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Platelet Count; Severity of Illness Index; Thrombocytopenia; Thrombopoiesis; Thrombopoietin

Acute myeloid leukemia in a 3 years old child with cleidocranial dysplasia. - Callea, Michele; Bellacchio, Emanuele; Fattori, Fabiana; Bertini, Enrico; Callea, Francesco; Cammarata-Scalisi, Francisco (Leuk Lymphoma, 2015)

Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

An adolescent with an altered state of mind. - Naviglio, Samuele; Papanti, Duccio; Moressa, Valentina; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Cannabinoids; Designer Drugs; Hallucinations; Humans; Male; Substance-Related Disorders

Advertisements of follow-on formula and their perception by pregnant women and mothers in Italy. - Cattaneo, Adriano; Pani, Paola; Carletti, Claudia; Guidetti, Margherita; Mutti, Valentina; Guidetti, Cecilia; Knowles, Alessandra (Arch Dis Child, 2015)
OBJECTIVE: To assess how follow-on formula milks for infants aged 6-12 months are presented to and understood by mothers. DESIGN: A quantitative and qualitative cross-sectional study including (1) an analysis of advertisements in three magazines for parents; (2) in-depth semistructured qualitative interviews to pregnant women on their perception of two advertisements for follow-on formula and (3) self-administered questionnaires for mothers to explore their exposure to and perception of formula advertisements. PARTICIPANTS: Eighty pregnant women 32-36 weeks of gestation with no previous children and 562 mothers of children <3 years old. SETTING: Maternal and child health centres in eight cities of Italy. RESULTS: Advertisements of formula (n=89) represented about 7% of all advertisements in the three magazines, the majority (58%) being for follow-on formula. Advertisements were parent-oriented, aimed at helping parents solve health problems of their babies or at eliciting good feelings, or both. The qualitative interviews to pregnant women showed inability to define the advertised products at first glance due to the ambiguity of the numeral 2 and the presumed age of the portrayed baby; this inability did not disappear after carefully viewing the advertisements and reading the text. When asked in the self-administered questionnaires whether they had ever come across advertisements of infant formula, 81% of mothers reported that they had, despite the legal inexistence of such advertisements, and 65% thought that it was for a product to be used from birth. CONCLUSIONS: Advertisements of follow-on formula are perceived by pregnant women and mothers as promoting infant formula.
Keywords: Adult; Advertising as Topic; Attitude to Health; Cross-Sectional Studies; Female; Humans; Infant; Infant Formula; Italy; Mothers; Perception; Periodicals as Topic; Pregnancy; Pregnant Women; Reading; Surveys and Questionnaires; Young Adult

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analgesia by cooling vibration during venipuncture in children with cognitive impairment. - Schreiber, Silvana; Cozzi, Giorgio; Rutigliano, Rosaria; Assandro, Paola; Tubaro, Martina; Cortellazzo Wiel, Luisa; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Children with cognitive impairment experience pain more frequently than healthy children and are more likely to require venipuncture or intravenous cannulation for various procedures. They are frequently unable to report pain and often receive poor pain assessment and management. This study assessed the effectiveness of physical analgesia during vascular access in children with cognitive impairments. METHODS: We conducted a prospective randomised controlled study at a tertiary-level children's hospital in Italy from April to May 2015 to assess whether a cooling vibration device called Buzzy decreased pain during venipuncture and intravenous cannulation in children with cognitive impairment. None of the children had verbal skills and the main cognitive impairments were cerebral palsy, epileptic encephalopathy and genetic syndromes. RESULTS: We tested 70 children with a median age of nine years: 34 in the Buzzy group and 36 in the no-intervention group. Parents were trained in the use of the Noncommunicating Children's Pain Checklist - postoperative version scale, and they reported no or mild procedural pain in 32 cases (91.4%) in the Buzzy group and in 22 cases (61.1%) in the no-intervention group (p = 0.003). CONCLUSION: Cooling vibration analgesia during vascular access reduced pain in children with cognitive impairment.

Analysis of functional variants reveals new candidate genes associated with alexithymia. - Mezzavilla, Massimo; Ulivi, Sheila; Bianca, Martina La; Carlino, Davide; Gasparini, Paolo; Robino, Antonietta (Psychiatry Res, 2015)
In this study we explored the possible association between 36,915 functional variants and alexithymia, a personality trait characterized by the inability to identify and describe emotions and feelings. From our analysis, variants in the genes ABCB4, TP53AIP1, ARHGAP32 and TMEM88B were identified linked to the alexithymia phenotype.
Keywords: Adolescent; Adult; Affective Symptoms; Aged; Case-Control Studies; DNA-Binding Proteins; Emotions; Female; Humans; Male; Membrane Proteins; Middle Aged; P-Glycoproteins; Personality Inventory; Phenotype; Tumor Suppressor Proteins; Young Adult

The anti-leukemic activity of sodium dichloroacetate in p53mutated/null cells is mediated by a p53-independent ILF3/p21 pathway. - Agnoletto, Chiara; Brunelli, Laura; Melloni, Elisabetta; Pastorelli, Roberta; Casciano, Fabio; Rimondi, Erika; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2015)
B-chronic lymphocytic leukemia (B-CLL) patients harboring p53 mutations are invariably refractory to therapies based on purine analogues and have limited treatment options and poor survival. Having recently demonstrated that the mitochondria-targeting small molecule sodium dichloroacetate (DCA) exhibits anti-leukemic activity in p53wild-type B-CLL cells, the aim of this study was to evaluate the effect of DCA in p53mutated B-CLL cells and in p53mutated/null leukemic cell lines. DCA exhibited comparable cytotoxicity in p53wild-type and p53mutated B-CLL patient cell cultures, as well as in p53mutated B leukemic cell lines (MAVER, MEC-1, MEC-2). At the molecular level, DCA promoted the transcriptional induction of p21 in all leukemic cell types investigated, including p53null HL-60. By using a proteomic approach, we demonstrated that DCA up-regulated the ILF3 transcription factor, which is a known regulator of p21 expression. The role of the ILF3/p21 axis in mediating the DCA anti-leukemic activity was underscored by knocking-down experiments. Indeed, transfection with ILF3 and p21 siRNAs significantly decreased both the DCA-induced p21 expression and the DCA-mediated cytotoxicity. Taken together, our results emphasize that DCA is a small molecule that merits further evaluation as a therapeutic agent also for p53mutated leukemic cells, by acting through the induction of a p53-independent pathway.

Appendicitis in children less than five years old: A challenge for the general practitioner. - Marzuillo, Pierluigi; Germani, Claudio; Krauss, Baruch S; Barbi, Egidio (World J Clin Pediatr, 2015)
Acute appendicitis is one of the most common indications for abdominal surgery in pediatrics with peak incidence in the second decade of life. Acute appendicitis in the first years of life is an uncommon event. The clinical presentation is often varied and the diagnosis may be overshadowed by other medical conditions. Gastroenteritis is the most common misdiagnosis, with a history of diarrhea present in 33% to 41% of patients. Pain is the most common presenting symptom in children less than 5 years old, followed by vomiting, fever, anorexia and diarrhea. The most common physical sign is focal tenderness (61% of the patients) followed by guarding (55%), diffuse tenderness (39%), rebound (32%), and mass (6%). Neonatal appendicitis is a very rare disease with high mortality; presenting symptoms are nonspecific with abdominal distension representing the main clinical presentation. The younger the patient, the earlier perforation occurs: 70% of patients less than 3 years develop a perforation within 48 h of onset of symptoms. A timely diagnosis reduces the risk of complications. We highlight the epidemiology, pathophysiology, clinical signs and laboratory clues of appendicitis in young children and suggest an algorithm for early diagnosis.

Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Assessment of the olfactory function in Italian patients with type 3 von Willebrand disease caused by a homozygous 253 Kb deletion involving VWF and TMEM16B/ANO2. - Cenedese, Valentina; Mezzavilla, Massimo; Morgan, Anna; Marino, Renato; Ettorre, Cosimo Pietro; Margaglione, Maurizio; Gasparini, Paolo; Menini, Anna (PLoS One, 2015)
Type 3 Von Willebrand disease is an autosomal recessive disease caused by the virtual absence of the von Willebrand factor (VWF). A rare 253 kb gene deletion on chromosome 12, identified only in Italian and German families, involves both the VWF gene and the N-terminus of the neighbouring TMEM16B/ANO2 gene, a member of the family named transmembrane 16 (TMEM16) or anoctamin (ANO). TMEM16B is a calcium-activated chloride channel expressed in the olfactory epithelium. As a patient homozygous for the 253 kb deletion has been reported to have an olfactory impairment possibly related to the partial deletion of TMEM16B, we assessed the olfactory function in other patients using the University of Pennsylvania Smell Identification Test (UPSIT). The average UPSIT score of 4 homozygous patients was significantly lower than that of 5 healthy subjects with similar sex, age and education. However, 4 other members of the same family, 3 heterozygous for the deletion and 1 wild type, had a slightly reduced olfactory function indicating that socio-cultural or other factors were likely to be responsible for the observed difference. These results show that the ability to identify odorants of the homozygous patients for the deletion was not significantly different from that of the other members of the family, showing that the 253 kb deletion does not affect the olfactory performance. As other genes may compensate for the lack of TMEM16B, we identified some predicted functional partners from in silico studies of the protein-protein network of TMEM16B. Calculation of diversity for the corresponding genes for individuals of the 1000 Genomes Project showed that TMEM16B has the highest level of diversity among all genes of the network, indicating that TMEM16B may not be under purifying selection and suggesting that other genes in the network could compensate for its function for olfactory ability.
Keywords: Adult; Case-Control Studies; Female; Genetic Association Studies; Homozygote; Humans; Italy; Male; Membrane Proteins; Middle Aged; Olfactory Mucosa; Olfactory Perception; Sequence Deletion; Smell; von Willebrand Disease, Type 3; von Willebrand Factor; Young Adult

Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Chagas, Bárbara Simas; Comar, Manola; Gurgel, Ana Pavla Almeida Diniz; Paiva, Sérgio; Seraceni, Silva; de Freitas, Antonio Carlos; Crovella, Sergio (PLoS One, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.

Acquired long QT syndrome: a focus for the general pediatrician. - Marzuillo, Pierluigi; Benettoni, Alessandra; Germani, Claudio; Ferrara, Giovanna; D'Agata, Biancamaria; Barbi, Egidio (Pediatr Emerg Care, 2014)
Acquired long QT syndrome (LQTS) is a disorder of cardiac repolarization most often due to specific drugs, hypokalemia, or hypomagnesemia that may precipitate torsade de pointes and cause sudden cardiac death. Common presentations of the LQTS are palpitations, presyncope, syncope, cardiac arrest, and seizures. An abnormal 12-lead electrocardiogram obtained while the patient is at rest is the key to diagnosis. The occurrence of drug-induced LQTS is unpredictable in any given individual, but a common observation is that most patients have at least 1 identifiable risk factor in addition to drug exposure. The cornerstone of the management of acquired LQTS includes the identification and discontinuation of any precipitating drug and the correction of metabolic abnormalities, such as hypokalemia or hypomagnesemia. Most of the episodes of torsade de pointes are short-lived and terminate spontaneously. We propose a management protocol that could be useful for the daily practice in the emergency pediatric department to reduce the risk of acquired QT prolongation.
Keywords: Adolescent; Death, Sudden, Cardiac; Electrocardiography; Female; General Practitioners; Humans; Long QT Syndrome; Ondansetron; Risk Factors; Serotonin Antagonists

Acute-onset pretibial swelling. - Lega, Sara; Rabusin, Marco; Pederiva, Federica (Indian Pediatr, 2014)
Keywords: Bone Marrow Diseases; Child, Preschool; Edema; Female; Granuloma Annulare; Humans; Leg; Tibia

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Assessment of coupling between trans-abdominally acquired fetal ECG and uterine activity by bivariate phase-rectified signal averaging analysis. - Casati, Daniela; Stampalija, Tamara; Rizas, Konstantinos; Ferrazzi, Enrico; Mastroianni, Cristina; Rosti, Eleonora; Quadrifoglio, Mariachiara; Bauer, Axel (PLoS One, 2014)
UNLABELLED: Couplings between uterine contractions (UC) and fetal heart rate (fHR) provide important information on fetal condition during labor. At present, couplings between UC and fHR are assessed by visual analysis and interpretation of cardiotocography. The application of computerized approaches is restricted due to the non-stationarity of the signal, missing data and noise, typical for fHR. Herein, we propose a novel approach to assess couplings between UC and fHR, based on a signal-processing algorithm termed bivariate phase-rectified signal averaging (BPRSA). METHODS: Electrohysterogram (EHG) and fetal electrocardiogram (fECG) were recorded non-invasively by a trans-abdominal device in 73 women at term with uneventful singleton pregnancy during the first stage of labor. Coupling between UC and fHR was analyzed by BPRSA and by conventional cross power spectral density analysis (CPSD). For both methods, degree of coupling was assessed by the maximum coefficient of coherence (CPRSA and CRAW, respectively) in the UC frequency domain. Coherence values greater than 0.50 were consider significant. CPRSA and CRAW were compared by Wilcoxon test. RESULTS: At visual inspection BPRSA analysis identified coupled periodicities in 86.3% (63/73) of the cases. 11/73 (15%) cases were excluded from further analysis because no 30 minutes of fECG recording without signal loss was available for spectral analysis. Significant coupling was found in 90.3% (56/62) of the cases analyzed by BPRSA, and in 24.2% (15/62) of the cases analyzed by CPSD, respectively. The difference between median value of CPRSA and CRAW was highly significant (0.79 [IQR 0.69-0.90] and 0.29 [IQR 0.17-0.47], respectively; p<0.0001). CONCLUSION: BPRSA is a novel computer-based approach that can be reliably applied to trans-abdominally acquired EHG-fECG. It allows the assessment of correlations between UC and fHR patterns in the majority of labors, overcoming the limitations of non-stationarity and artifacts. Compared to standard techniques of cross-correlations, such as CPSD, BPRSA is significantly superior.
Keywords: Electrocardiography; Female; Heart Rate, Fetal; Humans; Labor, Obstetric; Pregnancy; Uterine Contraction

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Association between orofacial granulomatosis and Crohn's disease in children: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Ventura, Alessandro (World J Gastroenterol, 2014)
AIM: To review pediatric cases of orofacial granulomatosis (OFG), report disease characteristics, and explore the association between OFG and Crohn's disease. METHODS: We conducted a systematic review according to the PRISMA guidelines. We searched Medline, LILACS, Virtual Health Library, and Web of Knowledge in September 2013 for cases of OFG in the pediatric age range (< 18 years), with no language limitations. All relevant articles were accessed in full text. The manual search included references of retrieved articles. We extracted data on patients' characteristics, disease characteristics, association with other diseases, and treatment. We analyzed the data and reported the results in tables and text. RESULTS: We retrieved 173 reports of OFG in children. Mean age at onset was 11.1 ± 3.8 years (range: 2.0-18 years). Prevalence in males was significant higher than in females (P < 0.001), with a male:female ratio of 2:1. Gastrointestinal signs or symptoms were present in 26.0% of children at the time of OFG diagnosis. Overall, 70/173 (40.4%) children received a concomitant diagnosis of Crohn's disease. In about half (51.4%) of the cases the onset of OFG anticipated the diagnosis of Crohn's disease, with a mean time between the two diagnoses of 13.1 ± 11.6 mo (range: 3-36 mo). Overall, 21/173 (12.1%) of the children with OFG had perianal disease, while 11/173 (6.4%) had a family history of Crohn's disease. Both perianal disease and a family history of Crohn's disease were significantly associated with a higher risk of Crohn's disease diagnosis in children with OFG [relative risk (RR) = 3.10, 95% confidence interval (CI): 2.46-3.90; RR = 2.74, 95%CI: 2.24-3.36, P < 0.0001 for both). Treatment of OFG included steroids (70.8% of children) and other immunosuppressive drugs (42.7%), such as azathioprine, thalidomide and infliximab. CONCLUSION: High prevalence of Crohn's disease in children with OFG suggests that OFG may be a subtype of Crohn's disease.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Crohn Disease; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Prevalence; Risk Factors; Steroids; Treatment Outcome

Association of CD209 and CD209L polymorphisms with tuberculosis infection in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; da Cruz, Heidi Lacerda Alves; Schindler, Haiana Charifker; Montenegro, Lilian Maria Lapa; Crovella, Sergio; Guimarães, Rafael Lima (Mol Biol Rep, 2014)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, is major cause of morbidity and mortality worldwide. So far, many candidate genes have been investigated for their possible association with TB. Dendritic cell-specific intercellular adhesion molecule 3 (ICAM-3) grabbing non-integrin (DC-SIGN) and Liver/lymph node-specific intercellular adhesion molecule-grabbing non-integrin (L-SIGN), encoded by CD209 and CD209L genes respectively, are known for binding to M. tuberculosis on human dendritic cells and macrophages. We screened 4 single nucleotide polymorphisms (SNPs) in the promoter region of CD209, namely -939G>A (rs735240), -871A>G (rs735239), -336A>G (rs4804803) and -139G>A (rs2287886) and tandem repeat polymorphisms in exon 4 of CD209 and CD209L genes looking for association with TB in a Northeastern Brazilian population (295 subjects, 131 TB patients and 164 healthy controls). The -139G>A and -939G>A SNPs were associated with susceptibility to TB, and in particular with pulmonary and extra-pulmonary forms respectively. The -871A>G and -336A>G SNPs were associated, the first with protection to both pulmonary and extra-pulmonary TB, the latter only with the pulmonary form. An association between GGAG haplotype and protection to TB infection was also found. Also tandem repeat polymorphism in CD209L exon 4 was associated with TB infection. This study provides evidence of an association between CD209 and CD209L polymorphisms and TB development in a Brazilian population, suggesting that variations in these genes may influence the protection and susceptibility to infection caused by M. tuberculosis.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; Cell Adhesion Molecules; Dendritic Cells; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Lectins, C-Type; Male; Mycobacterium tuberculosis; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tuberculosis; Young Adult

Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand

An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.

Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

Autosomal recessive Stickler syndrome due to a loss of function mutation in the COL9A3 gene. - Faletra, Flavio; d'Adamo, Adamo P; Bruno, Irene; Athanasakis, Emmanouil; Biskup, Saskia; Esposito, Laura; Gasparini, Paolo (Am J Med Genet A, 2014)
Stickler syndrome (STL) is a clinically variable and genetically heterogeneous syndrome characterized by ophthalmic, articular, orofacial, and auditory manifestations. STL has been described with both autosomal dominant and recessive inheritance. The dominant form is caused by mutations of COL2A1 (STL 1, OMIM 108300), COL11A1 (STL 2, OMIM 604841), and COL11A2 (STL 3, OMIM 184840) genes, while recessive forms have been associated with mutations of COL9A1 (OMIM 120210) and COL9A2 (OMIM 120260) genes. Type IX collagen is a heterotrimeric molecule formed by three genetically distinct chains: α1, α2, and α3 encoded by the COL9A1, COL9A2, and COL9A3 genes. Up to this time, only heterozygous mutations of COL9A3 gene have been reported in human and related to: (1) multiple epiphyseal dysplasia type 3, (2) susceptibility to an intervertebral disc disease, and (3) hearing loss. Here, we describe the first autosomal recessive Stickler family due to loss of function mutations (c.1176_1198del, p.Gln393Cysfs*25) of COL9A3 gene. These findings extend further the role of collagen genes family in the disease pathogenesis.
Keywords: Adolescent; Arthritis; Bone and Bones; Child; Child, Preschool; Collagen Diseases; Collagen Type IX; Connective Tissue Diseases; DNA Mutational Analysis; Facies; Female; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; Male; Mutation; Pedigree; Retinal Detachment

Acropustulosis of infancy. - Paloni, Giulia; Berti, Irene; Cutrone, Mario (Arch Dis Child Fetal Neonatal Ed, 2013)
Keywords: Acrodermatitis; Diagnosis, Differential; Female; Foot Dermatoses; Hand Dermatoses; Humans; Infant, Newborn

Amenorrhea in women treated with thalidomide: report of two cases and literature review. - Lazzerini, Marzia; Bramuzzo, Matteo; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Ventura, Alessandro (Inflamm Bowel Dis, 2013)
Keywords: Adolescent; Amenorrhea; Colitis, Ulcerative; Crohn Disease; Female; Humans; Review Literature as Topic; Thalidomide

Academy of breastfeeding medicine founder's lecture 2011: inequalities and inequities in breastfeeding: an international perspective. - Cattaneo, Adriano (Breastfeed Med, 2012)
Breastfeeding is the biological norm for infant feeding but is also a social construct. As such, its rates and practices are determined by the same social determinants that shape health inequalities and inequities. In the past 30 years, several reports have drawn attention to the changing pattern of breastfeeding inequalities across countries and population groups. Breastfeeding rates tend to fall and rise following a similar pattern everywhere, although at different times and speed. The role of women within families and societies, the routines of maternity hospitals and other healthcare services, and the pressure exerted by the baby food industry are among the factors that influence the time and speed of changes in breastfeeding rates and practices across countries and population groups. Inequities (i.e., inequalities considered unfair and avoidable by reasonable action) can be redressed by interventions for the protection, promotion, and support of breastfeeding. Evidence-based and quality-implemented support and promotion activities, if applied without an equity lens, may increase inequities. Activities for the protection of breastfeeding (e.g., implementation and enforcement of the International Code of Marketing of Breastmilk Substitutes; legislations, regulations, and policies to remove obstacles and barriers to good-quality breastfeeding support and to protect women and mothers in the workforce; elimination of obstacles and barriers to breastfeeding anywhere, anyhow, and anytime mothers want) apply to all women and are less dependent on take up by the target population. If well designed and enforced, protective interventions contribute to reducing inequalities and inequities and to delivering promotion and support activities more effectively.
Keywords: Breast Feeding; Cross-Cultural Comparison; Female; Health Policy; Health Promotion; Healthcare Disparities; Humans; Infant Food; Infant, Newborn; Internationality; Maternal Health Services; Mothers; Pregnancy; Socioeconomic Factors

Accuracy of diagnostic antibody tests for coeliac disease in children: summary of an evidence report. - Giersiepen, Klaus; Lelgemann, Monika; Stuhldreher, Nina; Ronfani, Luca; Husby, Steffen; Koletzko, Sibylle; Korponay-Szabó, Ilma R (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: The aim of this study was to summarise the evidence from 2004 to September 2009 on the performance of laboratory-based serological and point of care (POC) tests for diagnosing coeliac disease (CD) in children using histology as reference standard. PATIENTS AND METHODS: We searched MEDLINE and EMBASE for studies reporting on children for tests based on IgA and IgG anti-gliadin (AGA), endomysial (EmA), anti-transglutaminase-2 (TG2), and anti-deamidated gliadin peptides (DGP) antibodies or POC tests. For inclusion, histological analysis of duodenal biopsies and sensitivity and specificity for index tests had to be reported. Data were pooled and summary measures calculated for sensitivity, specificity, positive and negative likelihood ratios ("LR+", "LR-"), and diagnostic odds ratios (DOR). In case of elevated statistical heterogeneity, studies reaching 90% sensitivity or specificity were reported. RESULTS: A total of 2510 articles were reviewed; 16 entered meta-analysis, reporting on 3110 patients (1876 with CD, 1234 without CD). For IgA-EmA, sensitivity was ≥90% in 7/11 studies and pooled specificity 98.2%. For IgA-anti-TG2, 11/15 studies yielded sensitivities ≥90% and 13/15 specificities ≥90%. For IgA-DGP, sensitivity ranged between 80.7% and 95.1% (specificity 86.3%-93.1%); for IgG-DGP between 80.1% and 98.6% (specificity 86.0-96.9%). IgA-EmA had the highest pooled DOR (554) and LR+ (31.8) for a laboratory test, followed by IgA-anti-TG2, IgG-DGP, IgA-DGP and IgA-AGA. POC tests showed a pooled sensitivity of 96.4% for IgA-TG2 (specificity 97.7%). CONCLUSIONS: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.
Keywords: Autoantibodies; Biological Markers; Celiac Disease; Child; Gliadin; GTP-Binding Proteins; Humans; Immunoglobulin A; Immunoglobulin G; Point-of-Care Systems; Sensitivity and Specificity; Transglutaminases

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed

Acute febrile cholestatic jaundice in children: keep in mind Kawasaki disease. - Taddio, Andrea; Pellegrin, Maria Chiara; Centenari, Chiara; Filippeschi, Irene Pellegrini; Ventura, Alessandro; Maggiore, Giuseppe (J Pediatr Gastroenterol Nutr, 2012)
Kawasaki disease (KD) is characterized by persistent fever in addition to 4 of 5 signs of mucocutaneous inflammation. Although gastrointestinal involvement does not belong to the classic diagnostic criteria, it has been often associated with KD onset. We reviewed patients who were admitted for febrile cholestatic jaundice between 2003 and 2010 in 2 tertiary pediatric care centers. KD was the second most frequent cause (21%) after viral infections. Considering the relative high frequency of this condition, a high index of suspicion of KD should be maintained in patients presenting with febrile cholestatic jaundice.
Keywords: Child; Child, Preschool; Diagnosis, Differential; Female; Fever; Humans; Infant; Jaundice, Obstructive; Male; Mucocutaneous Lymph Node Syndrome; Virus Diseases

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Anti-leukemic activity of dasatinib in both p53(wild-type) and p53(mutated) B malignant cells. - Bosco, Raffaella; Rabusin, Marco; Voltan, Rebecca; Celeghini, Claudio; Corallini, Federica; Capitani, Silvano; Secchiero, Paola (Invest New Drugs, 2012)
The multi-kinase inhibitor dasatinib induced a variable but significant decrease of viability in both p53(wild-type) (EHEB, JVM-2, JVM-3) and p53(mutated) (MEC-1, MEC-2, BJAB) prolymphocytic B leukemic cells, due to a combination of cell cycle block in G1 and apoptosis. Antibody phospho-kinase array analysis revealed that dasatinib inhibited the phosphorylation of various kinases, including ERK1/2 and p38/MAPK as well as of STAT3 transcription factors, in both p53(wild-type) and p53(mutated) cells. Therefore, dasatinib might offer a novel therapeutic strategy not only for p53(wild-type), but also for p53(mutated) B malignancies that have the worst prognosis and urgently need innovative therapeutic approaches.
Keywords: Antineoplastic Agents; Apoptosis; B-Lymphocytes; Cell Line, Tumor; Cell Survival; G1 Phase Cell Cycle Checkpoints; Granulocyte Precursor Cells; Humans; Leukemia, Prolymphocytic, B-Cell; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Mutation; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Protein Kinase Inhibitors; Pyrimidines; STAT3 Transcription Factor; Thiazoles; Time Factors; Tumor Suppressor Protein p53

Application of reticulated platelets to transfusion management during autologous stem cell transplantation. - Parco, Sergio; Vascotto, Fulvia (Onco Targets Ther, 2012)
BACKGROUND: The immature (or reticulated) platelet fraction (IPF) is rich in nucleic acids, especially RNA, and can be used as a predictive factor for platelet recovery in platelet immunomediated consumption or in postchemotherapy myelosuppression. Our aim was to determine if transfusions with IPF-rich solutions, during autologous peripheral blood stem cell transplantation, reduce the occurrence of bleeding and hemorrhagic complications. PATIENTS AND METHODS: Transfusions were administered to 40 children, affected with hematological pathologies, who underwent autologous peripheral hematopoietic progenitor cell transplantation. There were two groups of 20 patients, one group treated with IPF-poor and the other with IPF-rich solutions. In the two groups, the conditioning regimen was the same for the same pathology (hematological pathologies: 14 acute lymphoblastic leukemia; twelve acute myelocytic leukemia; four non-Hodgkin's lymphoma; two Hodgkin's lymphoma; eight solid tumors). A new automated analyzer was used to quantify the IPF: the XE2100 (Sysmex, Kobe, Japan) blood cell counter with upgraded software. RESULTS: The 20 patients who received solutions with a high percentage of IPF (3%-9% of total number of infused platelets) required fewer transfusions than the 20 patients who received transfusions with a low percentage of IPF (0%-1% of total number of infused platelets): 83 versus 129 (mean of number of transfusions 4.15 versus 6.45) and a significant difference was found between the two groups by using the Mann-Whitney test (P < 0.001). The prophylactic transfusions decreased from three to two per week. There was only one case of massive hemorrhage. CONCLUSION: The use of IPF solutions reduces the number of transfusions and bleedings after peripheral blood stem cell transplantation in pediatric patients.

Asbestos and SV40 in malignant pleural mesothelioma from a hyperendemic area of north-eastern Italy. - Comar, Manola; Zanotta, Nunzia; Pesel, Giuliano; Visconti, Patrizia; Maestri, Iva; Rinaldi, Rosa; Crovella, Sergio; Cortale, Maurizio; De Zotti, Renata; Bovenzi, Massimo (Tumori, 2012)
AIMS AND BACKGROUND: Malignant mesothelioma is a fatal cancer of increasing incidence in north-eastern Italy. Together with asbestos, the polyomavirus SV40 was hypothesized to contribute to the onset of malignant mesothelioma. To investigate the putative role of SV40 in the individual susceptibility to asbestos-induced malignant mesothelioma, we conducted a molecular epidemiological study on a series of malignant mesothelioma patients from an area in north-eastern Italy hyperendemic for malignant pleural mesothelioma. METHODS AND STUDY DESIGN: We collected 63 mesothelioma samples from incidence cases of patients diagnosed with malignant pleural mesothelioma in the period 2009-2010. DNA was extracted from patients' tissue biopsies using the BioRobot EZ1 Qiagen workstation. SV40 sequence detection and quantification was performed by specific real time PCR. The 74.6% of the 63 enrolled patients had a history of asbestos exposure. The epithelioid histotype was more prevalent in males (64.0%) and the mixed in females (61.5%) who showed significantly higher cancer co-morbidity (46.1% vs 12%, P = 0.005). SV40 was detected in 22% of MM tumors, with a low viral load. In SV40-positive patients, a threefold increased risk of asbestos exposure was observed, more evident in females (OR 4.32) than in males (OR 1.20). CONCLUSIONS: Our findings indicate that a high prevalence of SV40 was present in malignant mesothelioma incident cases from an area hyperendemic for malignant mesothelioma in north-eastern Italy. Although asbestos is considered the main risk factor in malignant mesothelioma onset, a role for SV40 could be hypothesized.
Keywords: Adult; Aged; Asbestos; Carcinogens; Disease Susceptibility; DNA, Viral; Endemic Diseases; Female; Humans; Italy; Male; Mesothelioma; Middle Aged; Pleural Neoplasms; Polyomavirus Infections; Real-Time Polymerase Chain Reaction; Risk Factors; Simian virus 40; Tumor Virus Infections; Viral Load

Association between BclI polymorphism in the NR3C1 gene and in vitro individual variations in lymphocyte responses to methylprednisolone. - Cuzzoni, Eva; De Iudicibus, Sara; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (Br J Clin Pharmacol, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: In vitro lymphocyte steroid sensitivity has been suggested as a useful tool to predict in vivo response to glucocorticoid treatment in different inflammatory chronic diseases. A correlation between genetic polymorphisms and clinical response to glucocorticoids has been demonstrated in these patients. WHAT THIS STUDY ADDS: The BclI polymorphism in the glucocorticoid receptor (NR3C1) gene is associated with higher methylprednisolone potency in vitro. The combined evaluation of the in vitro sensitivity to methylprednisolone and BclI polymorphism could represent an aid for physicians to adjust therapy a priori. AIM To evaluate the association between the in vitro sensitivity of peripheral blood mononuclear cells (PBMCs) to methylprednisolone (MP) and the presence of genetic polymorphisms involved in glucocorticoid (GC) response. METHODS: In vitro MP inhibition of the proliferation of lymphocytes stimulated with concanavalin A was determined. Non linear regression of dose-response data was performed computing the MP concentration required to reduce proliferation to 50% (IC(50) ). The maximum inhibition achievable at the highest MP concentration (I(max) ) was also calculated. Moreover, the Taqman technique was used to analyze the BclI polymorphism in the NR3C1 gene and the Leu155His polymorphism in the NALP1 gene. RESULTS: A significant association between the BclI mutated genotype and an increased in vitro sensitivity to GCs was observed. CONCLUSIONS: The a priori evaluation of the BclI polymorphism, associated with a lymphocyte proliferation assay, could represent a useful diagnostic tool for the optimization of steroid treatment.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Apoptosis Regulatory Proteins; Cyclin D1; Dose-Response Relationship, Drug; Female; Genotype; Glucocorticoids; Humans; Lymphocytes; Male; Methylprednisolone; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Glucocorticoid; Young Adult

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

Association of MBL2 gene exon 1 variants with autoimmune thyroid disease in Brazilian patients. - Filho, C B; Rodrigues, F F; Segat, L; Fonseca, A M; Araujo, J; Arahata, C; Pontes, L; Vilar, L; de Lima Filho, J L; Crovella, S (Int J Immunogenet, 2012)
We investigated the association between MBL2 gene exon 1 functional polymorphisms and autoimmune thyroid disease (AITD) in 163 Brazilian patients (87 with Hashimoto thyroiditis, HT; 76 with Graves' disease) and 214 healthy controls. Individuals carrying MBL2 O allele are at higher risk of developing AITD (OR = 1.58, 95% CI: 1.11-2.26; P-value = 0.009) and HT (OR = 1.67, 95% CI: 1.09-2.55; P-value = 0.013) as suggesting a possible role for mannose-binding lectin in influencing disease susceptibility.
Keywords: Adolescent; Adult; Brazil; Case-Control Studies; Child; Child, Preschool; Exons; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Graves Disease; Hashimoto Disease; Humans; Infant; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Autoimmune-polyendocrinopathy-candidiasis-ectodermal-dystrophy in Calabria: clinical, immunological and genetic patterns. - Betterle, C; Ghizzoni, L; Cassio, A; Baronio, F; Cervato, S; Garelli, S; Barbi, E; Tonini, G (J Endocrinol Invest, 2012)
UNLABELLED: Autoimmune polyendocrinopathy-candidiasis-ectodermal- dystrophy (APECED), also known as autoimmune polyendocrine syndrome type 1 (APS-1), is a very rare disease. Diagnosis requires the presence of at least two of three major clinical features: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison's disease. DESIGN: In this study, we analyzed Autoimmune Regulator (AIRE) gene mutations and genotype-phenotype correlation in APECED patients originating from Calabria, a region in the south of Italy. PATIENTS AND METHODS: Four patients and their first-degree relatives were evaluated for clinical manifestations, autoantibody presence and AIRE gene mutations. RESULTS: Three patients carried a homozygous W78R mutation on exon 2, typical of patients with APECED from Apulia; the fourth patient had a homozygous R203X mutation on exon 5, typical of APECED patients from Sicily. Clinical disease expression showed wide variability. Analysis of relatives allowed the identification of 6 heterozygotes, none of whom showed major findings of APECED. CONCLUSIONS: No AIRE gene mutations specific to Calabria were found in patients with APS-1, but mutations similar to those in patients from Apulia and Sicily. Heterozygosity for AIRE gene mutation is not associated with major findings of APECED.
Keywords: Adolescent; Adult; Autoantibodies; Child; Female; Genetic Association Studies; Heterozygote; Homozygote; Humans; Italy; Male; Mutation; Polyendocrinopathies, Autoimmune; Prognosis; Sicily; Transcription Factors; Young Adult

Autologous cord blood harvesting in North Eastern Italy: ethical questions and emerging hopes for curing diabetes and celiac disease. - Parco, Sergio; Vascotto, Fulvia (Int J Gen Med, 2012)
BACKGROUND: The Friuli Venezia Giulia (FVG), a region of North Eastern Italy, has passed legislation (Decree No 2324/2010) to regulate the banking of umbilical cord blood samples for personal, autologous, or family-directed use, and to implement the Agreement of the State-Regions Permanent Conference (Decree No 62/CSR/2010). This paper aims to identify the formalities and the reasons why families collect and bank their cord blood in foreign banks for both personal and private use. METHODS: To this end, at the Institute for Maternal and Child Health of Trieste (the regional capital city of the FVG), Italy, which assists about 1800 pregnant women a year, 129 questionnaires, drafted from January 2010 to December 2011 and concerning the granting of authorization to export samples, were examined. RESULTS: The collected data showed that 75% of involved families had resorted to anonymous public collection, which is available to anyone with therapeutic needs, and provided compatibility and hematologic protocols recognized by the scientific and international community (main indications: leukemia, hemoglobinopaties, and inherited hematologic and immunologic disorders). Conversely, 25.0% requested private storage at a foreign bank for personal or family-dedicated use. The principal motivation by disease was for treatment for diabetes (22.4%) and celiac disease (19.7%) (a multiorgan disease for which the FVG region has provided safeguards by approving a specific law granting support to families; Decree No 561/2007). For these two types of disease we found that information was received from the internet and not from general medical physicians, with a significant difference found using the χ(2) test (P < 0.01). CONCLUSION: The indication of treating these diseases with cord blood stem cell transplantation appears to be well grounded and encouraging, and has recently been corroborated by the international literature; however, the economic and social motivations promoting cord blood storage, for a fee, in the event of diseases that are still under study, require accurate information through general medical physicians on the actual possibilities of treatment.

Avoidable interruptions during drug administration in an intensive rehabilitation ward: improvement project. - Buchini, Sara; Quattrin, Rosanna (J Nurs Manag, 2012)
AIMS: To record the frequency of interruptions and their causes, to identify 'avoidable' interruptions and to build an improvement project to reduce 'avoidable' interruptions. BACKGROUND: In Italy each year 30,000-35,000 deaths per year are attributed to health-care system errors, of which 19% are caused by medication errors. The factors that contribute to drug management error also include interruptions and carelessness during treatment administration. METHODS: A descriptive study design was used to record the frequency of interruptions and their causes and to identify 'avoidable' interruptions in an intensive rehabilitation ward in Northern Italy. A data collection grid was used to record the data over a 6-month period. RESULTS: A total of 3000 work hours were observed. During the study period 1170 interruptions were observed. The study identified 14 causes of interruption. CONCLUSIONS: The study shows that of the 14 cases of interruptions at least nine can be defined as 'avoidable'. An improvement project has been proposed to reduce unnecessary interruptions and distractions to avoid making errors. IMPLICATIONS FOR NURSING MANAGEMENT: An additional useful step to reduce the incidence of treatment errors would be to implement the use of a single patient medication sheet for the recording of drug prescription, preparation and administration and also the incident reporting.
Keywords: Attention; Drug Therapy; Feasibility Studies; Humans; Intensive Care Units; Italy; Medication Errors; Nursing Administration Research; Nursing Evaluation Research; Nursing Staff, Hospital; Patient Safety; Quality Assurance, Health Care; Rehabilitation Nursing; Safety Management; Time Factors

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

Acute cardiac valvular involvement in Kawasaki Disease. - Pellegrin, Maria Chiara; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2011)
Keywords: Adrenal Cortex Hormones; Child, Preschool; Female; Heart Valve Diseases; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant; Male; Mucocutaneous Lymph Node Syndrome; Treatment Outcome

Adam's rib and the origin of stem cells. - Callea, Francesco; Callea, Michele (Am J Hematol, 2011)
Keywords: Humans; Ribs; Stem Cell Transplantation; Stem Cells

Ages of celiac disease: from changing environment to improved diagnostics. - Tommasini, Alberto; Not, Tarcisio; Ventura, Alessandro (World J Gastroenterol, 2011)
From the time of Gee's landmark writings, the recent history of celiac disease (CD) can be divided into many ages, each driven by a diagnostic advance and a deeper knowledge of disease pathogenesis. At the same time, these advances were paralleled by the identification of new clinical patterns associated with CD and by a continuous redefinition of the prevalence of the disease in population. In the beginning, CD was considered a chronic indigestion, even if the causative food was not known; later, the disease was proven to depend on an intolerance to wheat gliadin, leading to typical mucosal changes in the gut and to a malabsorption syndrome. This knowledge led to curing the disease with a gluten-free diet. After the identification of antibodies to gluten (AGA) in the serum of patients and the identification of gluten-specific lymphocytes in the mucosa, CD was described as an immune disorder, resembling a chronic "gluten infection". The use of serological testing for AGA allowed identification of the higher prevalence of this disorder, revealing atypical patterns of presentation. More recently, the characterization of autoantibodies to endomysium and to transglutaminase shifted the attention to a complex autoimmune pathogenesis and to the increased risk of developing autoimmune disorders in untreated CD. New diagnostic assays, based on molecular technologies, will introduce new changes, with the promise of better defining the spectrum of gluten reactivity and the real burden of gluten related-disorders in the population. Herein, we describe the different periods of CD experience, and further developments for the next celiac age will be proposed.
Keywords: Autoantibodies; Celiac Disease; Diet, Gluten-Free; Gliadin; Glutens; History, 19th Century; History, 20th Century; History, 21st Century; History, Ancient; History, Medieval; Humans; Transglutaminases

Antibiotics in severely malnourished children: systematic review of efficacy, safety and pharmacokinetics. - Lazzerini, Marzia; Tickell, David (Bull World Health Organ, 2011)
OBJECTIVE: To systemically review the evidence in support of World Health Organization guidelines recommending broad-spectrum antibiotics for children with severe acute malnutrition (SAM). METHODS: CENTRAL, MEDLINE, EMBASE, LILACS, POPLINE, CAB Abstracts and ongoing trials registers were searched. Experts were contacted. Conference proceedings and reference lists were manually searched. All study types, except single case reports, were included. FINDINGS: Two randomized controlled trials (RCTs), one before-and-after study and two retrospective reports on clinical efficacy and safety were retrieved, together with 18 pharmacokinetic studies. Trial quality was generally poor and results could not be pooled due to heterogeneity. Oral amoxicillin for 5 days was as effective as intramuscular ceftriaxone for 2 days (1 RCT). For uncomplicated SAM, amoxicillin showed no benefit over placebo (1 retrospective study). The introduction of a standardized regimen using ampicillin and gentamicin significantly reduced mortality in hospitalized children (odds ratio, OR: 4.0; 95% confidence interval, CI: 1.7-9.8; 1 before-and-after study). Oral chloramphenicol was as effective as trimethoprim-sulfamethoxazole in children with pneumonia (1 RCT). Pharmacokinetic data suggest that normal doses of penicillins, cotrimoxazole and gentamicin are safe in malnourished children, while the dose or frequency of chloramphenicol requires adjustment. Existing evidence is not strong enough to further clarify recommendations for antibiotic treatment in children with SAM. CONCLUSION: Large RCTs are needed to define optimal antibiotic treatment in children with SAM with and without complications. Further research into gentamicin and chloramphenicol toxicity and into the pharmacokinetics of ceftriaxone and ciprofloxacin is also required.
Keywords: Anti-Bacterial Agents; Child; Child Nutrition Disorders; Child, Preschool; Humans; Severity of Illness Index; Treatment Outcome

Antidepressant drugs and breastfeeding: a review of the literature. - Davanzo, Riccardo; Copertino, Marco; De Cunto, Angela; Minen, Federico; Amaddeo, Alessandro (Breastfeed Med, 2011)
The use of antidepressants in breastfeeding mothers is controversial: Manufacters often routinely discourage breastfeeding for the nursing mother despite the well-known positive impact that breastfeeding carries on the health of the nursing infant and on his or her family and society. We conducted a systematic review of drugs commonly used in the treatment of postpartum depression. For every single drug two sets of data were provided: (1) selected pharmacokinetic characteristics such as half-life, milk-to-plasma ratio, protein binding, and oral bioavailability and (2) information about lactational risk, according to some authoritative sources of the literature: Drugs in Pregnancy and Lactation edited by Briggs et al. (Lippincott Williams, Philadelphia, 2008), Medications and Mothers' Milk by Hale (Hale Publishing, Amarillo, TX, 2010), and the LactMed database of TOXNET ( www.pubmed.gov ; accessed June 2010). Notwithstanding a certain variability of advice, we found that (1) knowledge of pharmacokinetic characteristics are scarcely useful to assess safety and (2) the majority of antidepressants are not usually contraindicated: (a) Selective serotinin reuptake inhibitors and nortryptiline have a better safety profile during lactation, (b) fluoxetine must be used carefully, (c) the tricyclic doxepine and the atypical nefazodone should better be avoided, and (d) lithium, usually considered as contraindicated, has been recently rehabilitated.
Keywords: Adrenergic Uptake Inhibitors; Antidepressive Agents; Antidepressive Agents, Tricyclic; Biological Availability; Breast Feeding; Depression, Postpartum; Directive Counseling; Drug Monitoring; Female; Humans; Infant, Newborn; Lactation; Lithium Compounds; Maternal Exposure; Milk, Human; Monoamine Oxidase Inhibitors; Pregnancy; Serotonin Uptake Inhibitors

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Atlanto-axial joint involvement as exclusive manifestation of juvenile idiopathic arthritis (JIA). - Taddio, A; Pellegrin, M C; Gregori, M; Wientroub, S; Padeh, S; Lepore, L (Clin Exp Rheumatol, 2011)
Keywords: Antirheumatic Agents; Arthritis, Juvenile; Atlanto-Axial Joint; Child; Dislocations; Female; Glucocorticoids; Humans; Magnetic Resonance Imaging; Pulse Therapy, Drug; Torticollis; Treatment Outcome; Uveitis

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Acute respiratory failure in a child after talc inhalation. - Patarino, Federica; Norbedo, Stefania; Barbi, Egidio; Poli, Furio; Furlan, Stefano; Savron, Fabio (Respiration, 2010)
Keywords: Female; Humans; Infant; Inhalation Exposure; Respiratory Insufficiency; Talc

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Analysis of DEFB1 regulatory SNPs in cystic fibrosis patients from North-Eastern Italy. - Segat, L; Morgutti, M; Athanasakis, E; Trevisiol, C; Amaddeo, A; Poli, F; Crovella, S (Int J Immunogenet, 2010)
Cystic fibrosis (CF) transmembrane regulator protein (CFTR) gene is undoubtedly the main genetic factor involved in the modulation of CF phenotype. However, other factors such as human defensins and the genes encoding for these antimicrobial peptides have been hypothesized as possible modifiers influencing airways infection in CF patients, but their role in the pathogenesis of lung disease is still debated. Since DEFB1 gene encoding for human beta-defensin 1 displays features such as antimicrobial or chemotactic activity playing a role in inflammation, it has been considered as a possible candidate CF modifier gene. We analysed three single nucleotide polymorphisms (SNPs) in the 5'-untranslated region of the DEFB1 gene (namely g-52G>A, g-44C>G and g-20G>A) in a group of 62 CF patients from North Eastern Italy, and in 130 healthy controls, with the aim of verifying the possible association of these functional SNPs with the pulmonary phenotype of CF patients. DEFB1 SNPs have been genotyped by using Taqman allele-specific fluorescent probes and a real-time PCR platform. No significant differences were found for allele, genotype and haplotype frequencies of DEFB1 g-52G>A, g-44C>G and g-20G>A SNPs in CF patients stratified for Pseudomonas aeruginosa infection, as well as in patients with a severe and mild clinical phenotype or in patients stratified for CFTR genotypes. DEFB1 allele, genotype and haplotype frequencies of CF patients globally considered were similar to those of healthy controls. Our findings are discordant with respect to another recent study performed on CF patients coming from Southern Italy, probably due to different ethnicity of the patients.
Keywords: 5' Untranslated Regions; Adolescent; Alleles; beta-Defensins; Case-Control Studies; Child; Child, Preschool; Chronic Disease; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Gene Frequency; Genotype; Haplotypes; Humans; Immunity, Innate; Infant; Infant, Newborn; Italy; Male; Polymorphism, Single Nucleotide; Pseudomonas Infections

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

Antimicrobial plant peptides isolated from native and crop species in Brazil: development of new drugs. - Crovella, Sergio (Curr Protein Pept Sci, 2010)
Keywords: Antimicrobial Cationic Peptides; Biodiversity; Brazil; Crops, Agricultural; Drug Discovery; Genomics; Plants

Atomic models for the polypeptide backbones of myohemerythrin and hemerythrin. - Hendrickson, W A; Ward, K B (Biochem Biophys Res Commun, 1975)
Keywords: Animals; Cnidaria; Computers; Hemerythrin; Metalloproteins; Models, Molecular; Muscle Proteins; Protein Conformation; Species Specificity